Crossing waters : undocumented migration in Hispanophone Caribbean and Latinx literature and art - Moreno, Marisel C., 1973- (University of Texas Press, 2022)
Debates over the undocumented migration of Latin Americans invariably focus on the southern US border, but most migrants never cross that arbitrary line. Instead, many travel, via water, among the Caribbean islands. The first study to examine literary and artistic representations of undocumented migration within the Hispanophone Caribbean, Crossing Waters relates a journey that remains silenced and largely unknown. Analyzing works by novelists, short-story writers, poets, and visual artists replete with references to drowning and echoes of the Middle Passage, Marisel Moreno shines a spotlight on the plight that these migrants face. In some cases, Puerto Rico takes on a new role as a stepping-stone to the continental United States and the society migrants will join there. Meanwhile the land border between Haiti and the Dominican Republic, the only terrestrial border in the Hispanophone Caribbean, emerges as a complex space within this cartography of borders. And while the Border Patrol occupies US headlines, the Coast Guard occupies the nightmares of refugees. An untold story filled with beauty, possibility, and sorrow, Crossing Waters encourages us to rethink the geography and experience of undocumented migration and the role that the Caribbean archipelago plays as a border zone.
Keywords: Illegal immigration in literature.; Emigration and immigration in art.; Caribbean literature (Spanish) -- Themes, motives.; Art, Caribbean -- Themes, motives.; Spanish American literature -- Themes, motives.; Art, Latin American -- Themes, motives.; Émigration et immigration dans l'art.; Littérature antillaise (espagnole) -- Thèmes, motifs.; Art antillais -- Thèmes, motifs.; Littérature hispano-américaine -- Thèmes, motifs.; Art latino-américain -- Thèmes, motifs.; SOCIAL SCIENCE / General; Art, Latin American -- Themes, motives; Caribbean literature (Spanish) -- Themes, motives; Emigration and immigration in art; Illegal immigration in literature; Spanish American literature -- Themes, motives; undocumented Americans, undocumented, undocumented migrants, migration, Central America, Central Americans, Dominican Republic, Haiti, Cuba, Hispanic Caribbean, cultural studies.; Electronic books.